2017
DOI: 10.1111/acer.13507
|View full text |Cite
|
Sign up to set email alerts
|

The Corticotropin Releasing Factor Receptor 1 in Alcohol Use Disorder: Still a Valid Drug Target?

Abstract: Corticotropin releasing factor (CRF) is a neuropeptide that plays a key role in behavioral and physiological responses to stress. A large body of animal literature implicates CRF acting at type 1 CRF receptors (CRFR1) in consumption by alcohol dependent subjects, stress-induced reinstatement of alcohol seeking, and possibly binge alcohol consumption. These studies have encouraged recent pilot studies of CRFR1 antagonists in humans with alcohol use disorder (AUD). It was a great disappointment to many in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 194 publications
0
33
0
Order By: Relevance
“…There are several recent reviews from 2016-2018 providing the details of other important stress responsive systems (like Corticotrophin Releasing Factor, Neuropeptide Y, and glucocorticoid receptor, etc.) from preclinical evidence to the recent clinical trials [Koob and Mason, 2016;Mantsch et al, 2016;Blaine and Sinha, 2017;Mason, 2017;Robinson and Thiele, 2017;Spierling and Zorrilla, 2017;Tunstall et al, 2017;Pomrenze et al, 2017]. The main focus in this mini-review is several other important stress responsive systems, which recently has not been reviewed, like arginine vasopressin/V1b receptors (Part I), and proopiomelanocortin/β-endorphin (Part II).…”
Section: Introductionmentioning
confidence: 99%
“…There are several recent reviews from 2016-2018 providing the details of other important stress responsive systems (like Corticotrophin Releasing Factor, Neuropeptide Y, and glucocorticoid receptor, etc.) from preclinical evidence to the recent clinical trials [Koob and Mason, 2016;Mantsch et al, 2016;Blaine and Sinha, 2017;Mason, 2017;Robinson and Thiele, 2017;Spierling and Zorrilla, 2017;Tunstall et al, 2017;Pomrenze et al, 2017]. The main focus in this mini-review is several other important stress responsive systems, which recently has not been reviewed, like arginine vasopressin/V1b receptors (Part I), and proopiomelanocortin/β-endorphin (Part II).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this single, well-validated target, no drug nor therapeutic options have been developed as treatments. One example of this for AUD is the corticotrophin releasing factor (CRF) system, which has tremendous research support for its involvement in AUD pathology, yet CRF inhibitors have produced disappointing results in double-blind, placebo controlled trials (Kwako et al 2015; Pomrenze et al 2017; Schwandt et al 2016). …”
Section: Traditional Approachmentioning
confidence: 99%
“…There are a number of possible reasons for this, including genetically heterogeneous human populations and the complexities of alcohol’s many targets (Most et al 2014; Pomrenze et al 2017). The brain is highly complex, and psychiatric diseases are characterized by numerous symptoms.…”
Section: Traditional Approachmentioning
confidence: 99%
“…Results from both clinic and preclinical studies have showed profound alterations of stress responsive systems after chronic alcohol abuse. Specifically, alcohol has direct or downstream effects on several hypothalamic stress‐responsive systems, including arginine vasopressin (AVP), oxytocin, corticotrophin releasing hormone (CRH) and their receptors, dynorphin and the kappa opioid receptors (KOP‐r) . The studies in both humans and rodents also provide clear support for the importance of these stress responsive systems in the process of alcohol consumption with strong interactions with hypothalamic‐pituitary‐adrenal (HPA) hormones and their receptors (eg, glucocorticoid receptors), especially after stress .…”
Section: Introductionmentioning
confidence: 99%